Strategic Responses to Myanmar’s Political Crisis: A Comparative Analysis of India and China’s Approaches - Jatmika, Muhammad Indrawan (Nation State: Journal of International Studies, 2025)
On February 1, 2021, Myanmar's military staged a coup, abruptly halting the country's political transition and triggering widespread violence, humanitarian distress, and regional instability. This article examines how India and China, with distinct political systems, foreign policy and strategic interests have responded to the crisis and shaped regional engagement in post-coup Myanmar. Adopting a qualitative approach, this study utilizes official government statements, news reports, and scholarly publications. The findings indicate that China has maintained close ties with the junta to secure its Belt and Road Initiative (BRI) investments, while also engaging with ethnic armed groups to ensure border stability and protect its economic assets. India, by contrast, follows a “dual-track” strategy—publicly supporting democratic norms but also maintaining relations with the military regime to safeguard its security and strategic interests. However, India's limited support for pro-democracy forces and restrictive refugee policies have weakened its regional credibility, while China’s pragmatic diplomacy allows it to preserve its influence and project strategic dominance in Myanmar. This comparative analysis highlights shifting China and India power dynamics in Southeast Asia and suggests that a more flexible and inclusive policy from both actors is crucial for contributing to Myanmar’s long-term stability and advancing their regional interests.